1987
DOI: 10.1080/00268978700101021
|View full text |Cite
|
Sign up to set email alerts
|

New anisotropic potential energy surfaces for N2-Ne and N2-Ar

Abstract: New anisotropic potential energy surfaces of the Hartree-Fock plus damped dispersion (HFD) type have been obtained for the N2-Ne and N2-Ar interactions. The SCF energies utilized in constructing the short-range part of the interactions were computed at 20 points on each surface by using basis sets of double zeta plus polarization quality. Anisotropic C 6 and Cs dispersion coefficients, utilized in constructing the long-range part of the interaction, have been calculated with a recently obtained combining rule.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

1988
1988
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(8 citation statements)
references
References 53 publications
1
6
1
Order By: Relevance
“…[6][7][8][9] The single minimum occurring for the T-shaped configuration for each of these potential surfaces has been confirmed by the ab initio results. A secondary minimum for the linear configuration is removed by the basis set superposition error correction.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…[6][7][8][9] The single minimum occurring for the T-shaped configuration for each of these potential surfaces has been confirmed by the ab initio results. A secondary minimum for the linear configuration is removed by the basis set superposition error correction.…”
Section: Discussionsupporting
confidence: 59%
“…Four previous potential surfaces [6][7][8][9] for the Ne-N 2 interaction, two of them fully empirical, 6,9 the other two semiempirical, 7,8 are available for use in theoreti-a͒ Present address: School of Chemistry, University of Melbourne, Parkville, Victoria 3052, Australia. cal simulations of the MW spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…The most thorough multiproperty check of an intermolecular potential energy surface for the N 2 /Ne interaction was performed by Wong et al 21 on the HFD3 PES. 25 These authors performed classical trajectory (CT) and infinite order sudden (IOS) calculations of an extensive set of effective cross sections governing a wide variety of transport and relaxation phenomena for Ne/N 2 mixtures. As far as we know, the only theoretical σ r,N2-Ne (T t ) data available are the CT values reported in this work, corresponding to the 77-673 K temperature interval; over this range, the CT cross sections grow also with decreasing T t .…”
Section: Dt R Dtmentioning
confidence: 99%
“…Mettes et al212 measured the Zeeman spectrum of Ar-02 and found that it was in somewhat better agreement with the modified potential of ref 211 than with the original one. McCourt et al 213 have extended the semiempirical models71 for He-N2 to obtain potentials for Ne-N2 and Ar-N2 and have tested the resulting potentials against experimental second virial coefficients; all their potentials have substantially more anisotropy in the position of the repulsive wall than the empirical potentials. Ling et al 214 have also developed semiempirical potentials for Ne-N2 and have compared calculated second virial coefficients, viscosities, and diffusion coefficients with experimental values.…”
Section: Specific Systemsmentioning
confidence: 99%